Modeling and Simulation of the Thickness Dependence in Die Casting Structures. Issue 1 (15th March 2018) - Martinez Page, Maria Angeles; Ruf, Matthias; Hartmann, Stefan
Abstract: Several die casting materials show different mechanical responses for specimens with different thicknesses. This can be observed in the variation of parameters, such as the Young's modulus, the tensile strength or hardness of the material in specimens with different thicknesses. In order to model this effect, we have experimentally investigated a specimen of a zinc die casting alloy. We concentrate in the modeling of the porosity distribution and its influence on the mechanical response using Mori‐Tanaka proposal for incorporating porosity. The applicability of the model is shown with a simulation example. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)